2019
DOI: 10.1097/mpg.0000000000002156
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sleep Disturbance and Disease Activity in Pediatric Patients With Inflammatory Bowel Disease

Abstract: Background: Pediatric patients with inflammatory bowel disease (IBD) are at risk for psychiatric symptoms that impact quality of life (QoL) and psychosocial functioning. Sleep disturbance has been reported to impose adverse effects on host defense mechanisms by affecting the magnitude and characteristics of the inflammatory response. The current study sought to assess the relationships among sleep disturbance, QoL, and psychosocial functioning in children with IBD. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Previous studies have demonstrated quality of life is negatively impacted in children with conditions and symptoms associated with SSADHD, including developmental delays, 4 epilepsy, 5 and sleep disturbances. 6 To date, however, there are no current research studies evaluating quality of life specifically in SSADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated quality of life is negatively impacted in children with conditions and symptoms associated with SSADHD, including developmental delays, 4 epilepsy, 5 and sleep disturbances. 6 To date, however, there are no current research studies evaluating quality of life specifically in SSADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies showed that sleep disorders promoted colonic inflammation and worsened the severity of colitis ( Preuss et al, 2008 ; Tang et al, 2009 ). Clinical studies showed a correlation of sleep disorders with IBD, in which a significant decrease in sleeping time and sleeping efficiency was closely related to the development and disease activity of IBD ( Chakradeo et al, 2018 ; Chrobak et al, 2018 ; Jarasvaraparn et al, 2019 ; Marinelli et al, 2020 ). A recent systematic review and meta-analysis confirmed the association between poor sleep quality and increased risk of IBD activity ( Hao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results concerning sleep quality in IBD patients are in line with former studies. Especially impairments regarding overall sleep quality and sleep disturbances in IBD patients have been shown for adults as well as for children and adolescents [28,[42][43][44][45][46]. However, Pirinen and colleagues (2010) revealed that significantly more adolescents with IBD (25%) had sleep problems than the control group (13%), according to parental report, whereas the adolescents themselves did not report elevated sleep difficulties [32].…”
Section: Sleep Quality Sleep Disturbances and Nightmare Effects In Adolescents With Ibdmentioning
confidence: 99%